(untitled) (Praxis Educativa, 2026)
This work aims to show how Educational Guidance has been developed in the Education of Youth and Adults in the province of Mendoza, Argentine Republic. This is a line of research carried out in the last decade at the National University of Cuyo that allows us to recognize the importance of this modality within Secondary Education, and the predominant role that the members of the Guidance Teams have played to optimize practices. teachers and student trajectories. In this journey, qualitative research has been carried out from documentary sources, interviews with key informants and case studies that allow the systematization of experiences considered “good practices” due to their relevance and institutional and community impact. The intention is to highlight the importance of forming interdisciplinary Guidance teams with pedagogical, psychological and social training in the Lifelong Education of Youth and Adults, necessary to guarantee the right to education. Keywords: Educational Guidance, Good Practices, Interdisciplinary Teams, Secondary Education, Youth and Adults.